Programa do operador econômico autorizado brasileiro: uma oportunidade de negócios - Silva Junior, Walter Thomaz da (2019)
This study presents the development and application of strategic planning for exploration of an opportunity brought by the Brazilian Authorized Economic Operator (AEOE), managed by the Brazilian Federal Revenue, which allows the reduction of operational costs for companies operating in the Brazilian foreign trade through the adaptation of its internal processes to the international standards of compliance in customs operations. In order to qualify themselves for the program, many companies operating in foreign trade will need specialized consultancy, considering the cost of getting involved in this process. This represents an opportunity for consultancies to offer support services to companies that benefit from this program. For this purpose, Portorium Consulting prepared itself to take advantage of this opportunity, whose process and actions are presented in this report, which starts from the characterization of the opportunity and the context in terms of markets, then presents the diagnosis and, finally, the final proposal of its use. The study contributes as a structured and implemented roadmap in the new product’s application in the area of foreign trade consultancy area. The innovation comes from the uniqueness of an international program (adopted by Brazil) of customs/tax compliance and of security in the international logistics chain.